A Sociologist on the Contribution of Mystique and Theology in Interreligious Dialogue - Callebaut, Bernhard (Religions, 2023)
One of the spectacular changes in the Catholic Church in the 1960s was her positive judgement on the other religions, as transmitted by the texts of the second Vatican Council (1962–1965). A sociologist is by profession interested in the diverse processes of cultural changes, and the birth of Catholic interreligious dialogue is therefore a very good case to study. For Catholics involved in interreligious dialogue, we can observe ideal-typically two attitudes at work that hinder a true dialogue between different religions: one is named ‘religious imperialism’ and the other is the contrary attitude, ‘religious indifferentism’. The present article studies how, in a crucial moment for the Catholic understanding of interreligious dialogue (around the year 2000), the mystical insights of Chiara Lubich (1920–2008), foundress of the Focolare Movement, alongside the theology of Piero Coda have made an interesting contribution to sustaining the process of change towards an always more convincing engagement in interreligious dialogue. In the context of the controversy on ‘Dominus Jesus’ (August 2000), they found a way to navigate between religious imperialism and religious indifferentism.